Visualizing and Understanding Hypothesis Testing Using Dynamic Software. Issue 2 (7th February 2020) - Gordon, Sheldon P.; Gordon, Florence S.
Abstract: This article illustrates ways that dynamic software using some sophisticated techniques in Excel can be used to demonstrate fundamental ideas related to hypothesis testing to increase student understanding of the concepts and methods in elementary statistics courses. The article considers hypothesis tests for the population mean with large or small samples, for the population proportion, for the difference of means, and for the difference of proportions. In each instance, spreadsheets are used that draw repeated random samples of selected sizes from a variety of underlying populations and display the sample means or sample proportions graphically. In the process, students come to see how the decision of rejecting or failing to reject the null hypothesis clearly depend on the sample drawn, which in turn depends on the size of the sample and the shape of the underlying population.